2015
DOI: 10.1128/mcb.00030-15
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Hepatocyte Nuclear Factor 4α Isoforms on Tumor Growth and T-Cell Factor 4/AP-1 Interactions in Human Colorectal Cancer Cells

Abstract: The nuclear receptor hepatocyte nuclear factor 4␣ (HNF4␣) is tumor suppressive in the liver but amplified in colon cancer, suggesting that it also might be oncogenic. To investigate whether this discrepancy is due to different HNF4␣ isoforms derived from its two promoters (P1 and P2), we generated Tet-On-inducible human colon cancer ( Thus, the HNF4␣ isoforms play distinct roles in colon cancer, which could be due to differential interactions with the Wnt/␤-catenin/TCF4 and AP-1 pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 107 publications
8
77
0
Order By: Relevance
“…Interestingly, a higher level of HNF4α was also associated with a lower level of Axin2 , a positive target of β‐catenin (Figure F). This corroborates previous studies performed by our laboratory and others suggesting that HNF4α could impair β‐catenin signalling . Altogether, these data suggest that loss of HNF4α in pretumoural hepatocytes with β‐catenin activation could play a part during hepatocarcinogenesis.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, a higher level of HNF4α was also associated with a lower level of Axin2 , a positive target of β‐catenin (Figure F). This corroborates previous studies performed by our laboratory and others suggesting that HNF4α could impair β‐catenin signalling . Altogether, these data suggest that loss of HNF4α in pretumoural hepatocytes with β‐catenin activation could play a part during hepatocarcinogenesis.…”
Section: Resultssupporting
confidence: 92%
“…This corroborates previous studies performed by our laboratory and others suggesting that HNF4α could impair β-catenin signalling. 8,12,21,25 Altogether, these data suggest that loss of HNF4α in pretumoural hepatocytes with β-catenin activation could play a part during hepatocarcinogenesis.…”
Section: Hnf4α Expression Was Impaired During Liver Carcinogenesis mentioning
confidence: 73%
“…The activation function 1 (AF‐1) domain at the N ‐terminus depicts the major difference between the P1‐HNF4α and P2‐HNF4α. The P2‐HNF4α lacks the AF‐1 domain and therefore is weaker than P1‐HNF4α regarding the transactivation activity . Additionally, P1‐HNF4α and P2‐HNF4α also differ in terms of tissue distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of P1‐HNF4α has been reported in hepatocellular carcinoma (HCC), colorectal carcinoma, and gastric carcinoma, during which P2 products are aberrantly elevated . P2‐HNF4α has been shown to promote inflammation and carcinogenesis in colon …”
Section: Introductionmentioning
confidence: 99%
“…For example, it was previously shown that HNF4A and TCF4 recognize considerable numbers of common DNA sequences and compete together to regulate the expression of these shared genes [82]. It is possible that this may be occurring for Hnf4a and Tcf3 TFs, and since we found the hepatic-specific factor Hnf4a to be up-regulated and Tcf3 to be down-regulated, the direct reprogramming process might be favored (Fig 4B and 4C).…”
Section: Discussionmentioning
confidence: 69%